Adhesion prevention material
Patent Information
- Application Number
- JP2024129920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-06
Smart Images

Figure 0007645523000005 
Figure 0007645523000006 
Figure 0007645523000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-adhesion material that can be suitably used to prevent adhesion of tissues where adhesions may occur. [Background technology]
[0002] Adhesion refers to a state in which tissues that should be separate are connected to each other, and it is said that adhesions occur in approximately 90% of patients who undergo surgery. Specifically, when the surface of an organ is damaged during surgery, an inflammatory reaction is induced, causing fibrin to precipitate, and fibrous adhesions are formed due to the inflammatory reaction induced by the absorption of fibrin, and angiogenesis and proliferation of fibroblasts progress, and the adhesions become further organized, becoming strong adhesions. When adhesions occur, complications such as organ dysfunction occur, and there is a risk of bleeding and organ damage due to adhesion removal operations during reoperations. Therefore, various adhesion prevention materials have been proposed to prevent adhesions. For example, Patent Document 1 proposes an adhesion prevention material that includes a sponge-like laminate applicable to a living body, which includes a first layer and a second layer of sponge-like low-endotoxin monovalent metal salt of alginic acid, at least a portion of which is crosslinked with a curing agent, and the weight-average molecular weight of the monovalent metal salt of alginic acid in the first layer is higher than the weight-average molecular weight of the monovalent metal salt of alginic acid in the second layer. Patent Document 2 proposes an adhesion prevention material that includes decellularized tissue and a biocompatible polymer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 138583 [Patent Document 2] International Publication No. 2016 / 143746 Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 1, the adhesion prevention effect of the adhesion preventing material is evaluated one week after organ damage is inflicted, and in Patent Document 2, the adhesion prevention effect of the adhesion preventing material is evaluated one week, four weeks, and one month after organ damage is inflicted. However, for example, in cases such as pediatric heart disease, surgery may be required every 3 to 12 months, and there is a demand for adhesion barriers that can reduce adhesions 3 to 12 months after cardiac surgery, improve surgical procedures such as adhesion removal, prevent organ damage, shorten the time required for reoperation, and reduce the burden on patients. There is therefore a demand for further improvements in the handleability and long-term adhesion prevention properties of adhesion barriers.
[0005] In order to solve the above-mentioned problems of the conventional art, the present invention provides an adhesion preventing material that has good handleability and improved long-term adhesion preventing properties. [Means for solving the problem]
[0006] The present invention relates to an adhesion preventing material comprising a fiber sheet and an oily agent adhered to the fiber sheet, the oily agent including liquid paraffin and a surfactant. Effect of the Invention
[0007] The present invention can provide an adhesion barrier that has good handling properties and has improved long-term adhesion prevention properties. Particularly preferably, the adhesion barrier of the present invention can be applied to the surface of cardiovascular blood vessels before each surgery, thereby making it possible to effectively prevent severe adhesion between the pericardium and the heart or myocardium. [Brief description of the drawings]
[0008] [Figure 1] 1 is an IR spectrum showing the analysis results of the nonwoven fabric (anti-adhesion material) of Example 1 by the FTIR-ATR method. [Diagram 2] 1 is an IR spectrum showing the analysis results of the nonwoven fabric of Comparative Example 1 by the FTIR-ATR method. [Diagram 3] 1 is an IR spectrum showing the analysis results of the oil solution used in Example 1 by the FTIR-ATR method. [Figure 4] 2 is a differential scanning calorimetry (DSC) curve showing the results of DSC measurement of the nonwoven fabric of Comparative Example 1 and the surfactant used in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The inventors of the present invention have conducted extensive research to solve the above-mentioned problems. As a result, they have found that by using an adhesion inhibitor in which an oil agent containing liquid paraffin and a surfactant is attached to a fiber sheet, the adhesion inhibitor has good handleability and long-term adhesion prevention properties. Specifically, it is presumed that the adhesion inhibitor has good handleability due to the use of a fiber sheet as a substrate, and that the long-term adhesion prevention properties have been improved by the combined use of liquid paraffin and a surfactant as an oil agent. In particular, it has been confirmed that the adhesion inhibitor effectively suppresses severe adhesion over a long period of time (e.g., after 3 months) after application to the surface of a wound site in the heart, and that the pericardium can be peeled off from the heart or myocardium without bleeding, and can be suitably used in cases where surgery is required every 3 months, such as in pediatric heart disease.
[0010] In this specification, when a numerical range is indicated by "-", the numerical range includes both end values (upper and lower limits). For example, a numerical range of "A to B" includes both end values A and B, and is the same range as "A or more and B or less". Any number within the range or any range contained within the range is specifically disclosed. In addition, when multiple numerical ranges are described in this specification, they are intended to include numerical ranges that appropriately combine the upper and lower limits of different numerical ranges.
[0011] The adhesion prevention material includes a fiber sheet. In one or more embodiments of the present invention, the fibers constituting the fiber sheet are preferably composed mainly of a biocompatible polymer. In one or more embodiments of the present invention, the term "main component" refers to a component that is contained in an amount of 80% by mass or more. In one or more embodiments of the present invention, the term "biocompatibility" refers to biodegradability that is broken down and metabolized in the body and disappears, or to remaining in the body without breaking down and not adversely affecting biological functions. Examples of biodegradable polymers include, but are not limited to, polylactic acid (PLA), polyglycolic acid (PGA), ε-polycaprolactone (PCL), alginate, collagen, and gelatin. Examples of biocompatible polymers that can be placed in the body include, but are not limited to, PGA, alginate, collagen, cellulose, carboxymethylcellulose, and gelatin.
[0012] The fibers constituting the fiber sheet preferably contain 85% by mass or more of the biocompatible polymer, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may be substantially 100% by mass. In addition to the biocompatible polymer, the fibers constituting the fiber sheet may contain 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less of other components, as necessary. The other components may be crosslinkers, plasticizers, other additives, and the like.
[0013] From the viewpoint of strength and biocompatibility, the fibers constituting the fiber sheet preferably contain polyglycolic acid as a main component, preferably contain 80% by mass or more of polyglycolic acid, more preferably contain 85% by mass or more, even more preferably contain 90% by mass or more, even more preferably contain 95% by mass or more, and may be substantially 100% by mass. In addition to polyglycolic acid, the fibers containing polyglycolic acid as a main component may contain other components in an amount of 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less, as necessary. The other components may be the above-mentioned biocompatible polymers other than polyglycolic acid, or may be crosslinkers, plasticizers, other additives, and the like.
[0014] The fibers constituting the fiber sheet may be long fibers or short fibers. Long fibers can be obtained by forming the biocompatible polymer into fibers by any suitable spinning method such as melt spinning, dry spinning, or wet spinning. Short fibers can be obtained by cutting long fibers to a predetermined length, for example, 100 mm or less, or 25 to 78 mm.
[0015] The single fiber fineness of the fibers constituting the fiber sheet is not particularly limited, but from the viewpoints of biodegradability and fiber strength, it is preferably 1 to 50 dtex, more preferably 2 to 10 dtex, and even more preferably 3 to 7 dtex.
[0016] The shape of the fiber sheet is not particularly limited, and examples thereof include woven fabrics, knitted fabrics, nonwoven fabrics, and composites thereof. The woven fabric may be a staple fiber woven fabric obtained by spun a staple fiber having the biocompatible polymer as a main component by a normal method and then weaving the same by a normal method, or a long fiber woven fabric obtained by weaving a long fiber having the biocompatible polymer as a main component by a normal method. The knitted fabric may be a staple fiber knitted fabric obtained by spun a staple fiber having the biocompatible polymer as a main component by a normal method and then knitting the same by a normal method, or a long fiber knitted fabric obtained by knitting a long fiber having the biocompatible polymer as a main component by a normal method.
[0017] The nonwoven fabric may be obtained by forming short fibers mainly composed of the biocompatible polymer into a sheet-like web using a carding machine or the like, and then entangling or bonding (adhering) the fibers of the resulting web by needle punching or hot molding to fix the shape.
[0018] The nonwoven fabric may also be a spunbonded nonwoven fabric obtained by collecting fibers mainly composed of the biocompatible polymer directly on the surface of a net or roller without winding immediately after spinning. The nonwoven fabric may also be a meltblown nonwoven fabric obtained by melting the biocompatible polymer, then discharging the resulting molten or solution of the biocompatible polymer from a nozzle while blowing it off with compressed air or the like, and collecting it on the surface of a net or roller, or a flash-spun nonwoven fabric obtained by dissolving the biocompatible polymer in a solvent, then discharging the resulting solution of the biocompatible polymer from a nozzle while blowing it off with compressed air or the like, and collecting it on the surface of a net or roller. In particular, a nonwoven fabric in which long fibers (filaments) are knitted with a knitting machine and then needle-punched to intertwine the fibers is preferred as a shape that makes it difficult for fiber pieces to fall off inside the body during and after surgery.
[0019] The adhesion preventing material includes an oily agent attached to the fiber sheet. In the adhesion preventing material, the oily agent composed of liquid paraffin and a surfactant is attached in an amount of preferably 0.1 to 20% by mass, more preferably 0.2 to 15% by mass, and even more preferably 0.3 to 10% by mass, relative to the mass of the fiber sheet. When the amount of oily agent attached is 0.1% by mass or more, the occurrence of severe adhesion can be effectively suppressed over a long period of time (e.g., after 3 months) after the adhesion preventing material is applied to the surface of tissue where adhesion may occur, such as a wound. When the amount of oily agent attached is 20% by mass or less, the sheet is prevented from slipping off when grasped with tweezers or the like, or from sliding away from the application site during surgery, and good handleability can be ensured.
[0020] The blending amounts of liquid paraffin and surfactant in the oil agent are not particularly limited; however, for example, from the viewpoint of easily exerting a synergistic effect between the liquid paraffin and the surfactant, when the total of the liquid paraffin and the surfactant is taken as 100 mass%, the oil agent preferably contains 30 to 90 mass% of liquid paraffin and 10 to 70 mass% of surfactant, and more preferably contains 50 to 70 mass% of liquid paraffin and 30 to 50 mass% of surfactant.
[0021] The liquid paraffin is a mixture of hydrocarbons obtained from petroleum crude oil through processes such as distillation and refining, and is not particularly limited as long as it is liquid at room temperature (5 to 40°C) and normal pressure (101325 Pa). The number of carbon atoms of the hydrocarbon is not particularly limited, and may be, for example, 15 or more, 20 or more, or 20 to 45. There is no particular limit to the presence or absence of double bonds in the hydrocarbon, but those containing a large amount of saturated hydrocarbons are preferably used. Furthermore, the structure of the hydrocarbon may include any of straight chain, branched chain, and cyclic structures, and liquid paraffin of any specific gravity may be used. In particular, liquid paraffin and light liquid paraffin listed in the Japanese Pharmacopoeia are preferred, and light liquid paraffin is more preferred. In addition, it may contain an appropriate type of tocopherol as a stabilizer. The liquid paraffin may be used alone or in combination of two or more types.
[0022] From the viewpoint of enhancing the dispersibility of liquid paraffin, the surfactant is preferably a nonionic surfactant, and more preferably a polyoxyethylene alkyl ether. The average degree of polymerization of the ethylene oxide group in the polyoxyethylene alkyl ether may be 5 to 50. Specific examples of the polyoxyethylene alkyl ether include polyoxyethylene lauryl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene cetyl ether, polyoxyethylene oleyl ether, and polyoxyethylene stearyl ether. The surfactant may be used alone or in combination of two or more.
[0023] From the viewpoint of enhancing the synergistic effect with liquid paraffin and further improving the adhesion prevention property over a long period of time (for example, after 3 months) after application of the adhesion preventing material to the surface of tissues where adhesion may occur, such as wounds, the surfactant preferably has intermediate water (hereinafter, also simply referred to as intermediate water) in which an exothermic peak due to low-temperature crystallization of water is observed at 0°C or less during the temperature rise process in differential scanning calorimetry (DSC) when wet, more preferably a nonionic surfactant having intermediate water when wet, and more preferably a polyoxyethylene alkyl ether having intermediate water when wet. In this specification, "when wet" means a state in which moisture is attached to the extent that it exists on the surface of an organ in a living body, and for example, the surfactant can be wetted as described in the Examples. From the viewpoint of easily having intermediate water when wet, the polyoxyethylene alkyl ether preferably contains polyoxyethylene oleyl ether.
[0024] In this specification, the amount of oil adhering to the fiber sheet can be measured by the method described in 8.27 Solvent Extraction in JIS L 1013 Chemical Fiber Filament Yarn Test Method (2018). When the amount of oil applied to the fiber sheet during the manufacturing process can be confirmed, it may be regarded as the amount of oil adhering to the fiber sheet of the obtained product.
[0025] The method of applying the oil (liquid paraffin and surfactant) to the fiber sheet is not particularly limited as long as the oil can be applied to the fiber sheet. For example, when applying the oil to the fiber sheet, an oil composition containing an oil and water can be used. Specifically, for example, an oil composition containing an oil and water may be applied to fibers as a spinning oil in the spinning process, and then the fibers to which the oil has been applied may be dried to produce a fiber sheet; in the weaving or knitting process, an oil composition containing an oil and water may be applied to spun yarn before or after the yarn path, and then the fiber sheet may be dried to apply the oil to the fiber sheet. Alternatively, an oil composition containing an oil and water may be applied in a post-treatment of woven fabrics, knitted fabrics, and nonwoven fabrics, and then the fiber sheet may be dried to apply the oil to the fiber sheet. The method of applying the oil composition containing an oil and water to fibers, spun yarns, woven fabrics, knitted fabrics, and nonwoven fabrics is not particularly limited, and may be any of dipping, coating, spraying, and the like. The drying method after application of the oil composition is not particularly limited, and can be, for example, air drying or drying in a dryer. In the oil composition, liquid paraffin is emulsified and dispersed in water by the surfactant. Therefore, the liquid paraffin and the surfactant can be uniformly applied to the fiber sheet. From the viewpoint of uniformly applying the liquid paraffin and the surfactant to the fiber sheet and easily exerting the synergistic effect of the liquid paraffin and the surfactant, the oil composition preferably contains 5 to 10 mass% liquid paraffin, 2 to 10 mass% surfactant, and 80 to 93 mass% water, and more preferably contains 6 to 9 mass% liquid paraffin, 3 to 8 mass% surfactant, and 83 to 91 mass% water.
[0026] A method for applying an oil to a polyglycolic acid long fiber nonwoven fabric, which is a preferred example of a fiber sheet, will be described below.
[0027] The polyglycolic acid long fiber nonwoven fabric preferably contains 90% by mass or more, more preferably 95% by mass or more, of polyglycolic acid. The polyglycolic acid long fiber nonwoven fabric may be substantially composed of 100% by mass of polyglycolic acid. The polyglycolic acid long fiber nonwoven fabric may contain, in addition to polyglycolic acid, 10% by mass or less, or 5% by mass or less of other components, as necessary. The other components may be the above-mentioned biocompatible polymers other than polyglycolic acid, or may be crosslinking agents, plasticizers, other additives, and the like.
[0028] The polyglycolic acid long fiber nonwoven fabric is not particularly limited, but from the viewpoint of increasing the tensile strength, it is preferably a long fiber needle-punched nonwoven fabric obtained by needle-punching a knitted or woven fabric made of polyglycolic acid long fibers, and more preferably a long fiber needle-punched nonwoven fabric obtained by needle-punching a knitted fabric (also called knitted fabric) made of polyglycolic acid long fibers. The knitted fabric may be either weft knitted or circular knitted.
[0029] Specifically, the oil can be applied to the polyglycolic acid long fiber nonwoven fabric as follows. (1) An oil composition, specifically an oil composition containing 5 to 10% by mass of liquid paraffin, 2 to 10% by mass of a surfactant, and 80 to 97% by mass of water, is sprayed onto the polyglycolic acid long fibers with a spray, and then the polyglycolic acid long fibers are air-dried to adhere the oil to the polyglycolic acid long fibers. (2) The polyglycolic acid filaments to which the oil has been applied are woven to produce a woven fabric. (3) A polyglycolic acid long fiber needle-punched nonwoven fabric is produced by needle-punching the knitted or woven fabric. If necessary, multiple knitted or woven fabrics may be stacked together to a predetermined thickness, and then the needle-punched nonwoven fabric may be subjected to needle-punching.
[0030] From the viewpoint of excellent long-term adhesion prevention properties (e.g., adhesion prevention properties after 3 months) when applied to tissues where adhesion may occur, such as wounds, the adhesion prevention material is selected from the group consisting of a material having a wavelength of 2860 cm in an analysis by Fourier transform ultraviolet spectroscopy (FTIR)-ATR (attenuated total reflectance) and a material having a wavelength of 2860 cm in an analysis by FTIR (Fourier transform ultraviolet spectroscopy)-ATR (attenuated total reflectance) method.-1 It is preferable that the peak derived from the oil agent is present in the vicinity.
[0031] The bending resistance of the adhesion prevention material is not particularly limited, but from the viewpoint of improving handleability when applied to tissues where adhesion may occur, such as wounds, the bending resistance measured by the 41.5° cantilever method is preferably 20 to 80 mm, and more preferably 25 to 70 mm.
[0032] The basis weight of the adhesion preventing material is not particularly limited, but is preferably 10 to 200 g / m from the viewpoint of improving the handling property and adhesion prevention property when applied to tissues where adhesion may occur, such as wounds. 2 It is preferable that the thickness is 20 to 180 g / m 2 More preferably, the thickness is 30 to 160 g / m 2 More preferably, the thickness is 40 to 140 g / m 2 It is particularly preferred that:
[0033] The thickness of the adhesion preventing material is not particularly limited, but from the viewpoint of improving handleability and adhesion prevention properties when applied to tissues where adhesion may occur, such as wounds, the thickness is preferably 0.1 to 2.0 mm, more preferably 0.2 to 1.8 mm, even more preferably 0.3 to 1.6 mm, and particularly preferably 0.4 to 1.4 mm.
[0034] The tensile strength of the adhesion preventing material is not particularly limited, but from the viewpoint of improving handleability and adhesion prevention properties when applied to tissue where adhesion may occur, such as wounds, it is preferably 2 to 50 N, more preferably 5 to 40 N, and even more preferably 10 to 20 N. Furthermore, when the adhesion preventing material has a tensile strength of 10 N or more, it also provides good suturing properties after application to the surface of tissue where adhesion may occur, such as wounds.
[0035] The breaking elongation of the adhesion preventing material is not particularly limited, but from the viewpoint of improving handleability and adhesion prevention properties when applied to tissues where adhesion may occur, such as wounds, it is preferably 100 to 1000%, more preferably 200 to 700%, and even more preferably 300 to 500%.
[0036] The adhesion preventing material has high long-term adhesion preventing properties when applied to tissues where adhesions may occur, and preferably has an adhesion score of 2 or less both 3 months and 6 months after application to a wound in the heart. In this specification, the adhesion score is determined based on the degree of necessary detachment of the pericardium, and the degree of crushing and bleeding of the cardiac surface and / or myocardium, and an adhesion score of 2 or less means that there is no bleeding at the time of detachment. The adhesion score can be specifically evaluated and determined as described in the Examples.
[0037] The adhesion barrier can be applied to targets requiring adhesion prevention, such as tissues where adhesions may occur, to suppress adhesions and prevent severe adhesions. The fibers constituting the fiber sheet are mainly composed of biocompatible polymers, and therefore are excellent in safety. The adhesion barrier is applied to tissues where adhesions may occur, such as wounds, and suppresses severe adhesions both 3 months and 6 months later, providing excellent long-term adhesion prevention properties.
[0038] Examples of tissues in which adhesions may occur include tissues whose organ surfaces have been damaged in surgery, tissues whose surfaces have become inflamed or may become inflamed due to drying in surgery, etc. Specific examples of tissues in which adhesions may occur include the pericardium, heart, epicardium, pleura, abdominal wall, peritoneum, bladder, amniotic membrane, uterus, dura mater, diaphragm, small intestine, large intestine, stomach, anus, pancreas, spleen, liver, kidney, lung, skin, esophagus, ligament, and tendon, and preferred examples include the pericardium and abdominal wall.
[0039] The adhesion preventing material is preferably prepared in an appropriate size according to the area, shape, irregularities, etc. of the surface of the tissue where adhesions may occur, and is applied to the surface of the tissue where adhesions may occur. After the adhesion preventing material is applied to the surface of the tissue where adhesions may occur, the adhesion preventing material and the surface of the tissue where adhesions may occur may be sutured together, if necessary. Since the adhesion preventing material contains a fiber sheet, the suture strength is high.
[0040] The adhesion barrier may be used for humans or for organisms other than humans. The organisms other than humans may be, for example, birds or non-human mammals. Examples of non-human mammals include cows, monkeys, cats, mice, rats, guinea pigs, hamsters, ferrets, pigs, dogs, rabbits, sheep, goats, and horses.
[0041] Before, simultaneously with, or after application of the adhesion barrier to tissues where adhesions may occur, concomitant drugs such as antibiotics, such as streptomycin, penicillin, tobramycin, amikacin, gentamicin, neomycin, and amphotericin B, aspirin, nonsteroidal antipyretic analgesics (NSAIDs), and anti-inflammatory drugs, such as acetaminophen, may be administered. These drugs may be mixed into the adhesion barrier. Since the adhesion barrier contains a fiber sheet, the drug is easily impregnated.
[0042] By impregnating the adhesion barrier with a drug solution and administering it, it is possible to simultaneously achieve adhesion prevention and local sustained release of the drug in the abdominal cavity, thoracic cavity, cardiac cavity, subarachnoid cavity, serous cavity (peritoneal cavity, pleural cavity, pericardial cavity), joint cavity, etc. Furthermore, by carrying the drug in layers with different dissolution rates, it is also possible to release the drug at a fast sustained release rate and a slow sustained release rate. EXAMPLES
[0043] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples.
[0044] The measurement and evaluation methods used in the examples and comparative examples will be described below.
[0045] (Met) Measured according to JIS L 1913:2018 6.2 Weight per unit area (ISO method).
[0046] (Thickness) Measured using JIS L 1913:2018 6.1 Thickness (ISO method) Method B.
[0047] (bending resistance) The bending resistance of the nonwoven fabric was measured by the 41.5° cantilever method (ISO method) of JIS L 1913:2010 6.7.
[0048] (Tensile strength) Measured according to JIS L 1913:2018 6.3 Tensile strength and elongation (ISO method).
[0049] (Elongation at break) Measured according to JIS L 1913:2018 6.3 Tensile strength and elongation (ISO method).
[0050] (Differential Scanning Calorimetry) Using a differential scanning calorimeter DSC7000X (Hitachi High-Tech Science Corporation), the temperature was lowered from 30°C to -100°C at a rate of 5°C per minute, and then the temperature was raised from -100°C to 50°C at a rate of 5°C per minute, and then the temperature was held for 1 minute. In the case of surfactants, the surfactant to be measured was added with twice the amount of pure water, left for one week to absorb water, and then left to stand in a thermostatic chamber at 45°C for 12 hours to moisten it, and then 3 to 5 mg of the moist surfactant was placed in an aluminum pan and sealed with an autosealer for measurement. In the case of fiber sheets, the sheet was cut with scissors to a fiber length (about 3 mm) that would fit in the aluminum pan, and 3 to 5 mg of the cut fibers were placed in the aluminum pan, and then covered with a highly breathable nonwoven fabric and air-dried for 12 hours at room temperature of 25°C. After drying, the aluminum pan was sealed with an autosealer for measurement.
[0051] (Fourier transform ultraviolet spectroscopy - total reflection measurement method) Using a Fourier transform ultraviolet spectrophotometer FT / IR-4200 (manufactured by JASCO Corporation), the ATR method was used at a wave number of 4000 cm -1 From 500cm -1 The infrared transmittance was measured in the range.
[0052] Example 1 An oil composition consisting of 8 mass% liquid paraffin, 2 mass% polyoxyethylene oleyl ether 1 (average degree of polymerization of ethylene oxide groups: 16), 2 mass% polyoxyethylene oleyl ether 2 (average degree of polymerization of ethylene oxide groups: 20), and 88 mass% water was sprayed onto polyglycolic acid long fibers (multifilament yarn, number of filaments: 10, single fiber fineness: 5.5 dtex, total fineness: 55 dtex) by spraying, and then air-drying in a room at room temperature of 25°C to adhere 0.5 mass% of an oil consisting of liquid paraffin, polyoxyethylene oleyl ether 1, and polyoxyethylene oleyl ether 2 (mass ratio: liquid paraffin: polyoxyethylene oleyl ether 1: polyoxyethylene oleyl ether 2 = 8:2:2) to the polyglycolic acid long fibers. Thereafter, the polyglycolic acid long fibers to which the oil had been adhered were used to knit a fabric (basis weight: 20 g / m) on a circular knitting machine. 2 The resulting knitted fabric was laid flat, and four pieces were stacked on top of each other while being careful not to create wrinkles, and then needle punched to produce a fabric with a thickness of 0.61 mm and a basis weight of 81 g / m2. 2 Thus, a needle-punched nonwoven fabric of the above formula was obtained.
[0053] Comparative Example 1 A needle-punched nonwoven fabric obtained in the same manner as in Example 1 was ultrasonically cleaned in ethanol to remove the oils (liquid paraffin and polyoxyethylene oleyl ether), and then dried to obtain a nonwoven fabric.
[0054] Comparative Example 2 A tissue substitute artificial fiber cloth made of commercially available PGA (weight 32 g / m 2 A sheet having a thickness of 0.15 mm and manufactured by Gunze Medical Japan Ltd., product name "Neoveil (registered trademark)" sheet, 015 type) was used.
[0055] Comparative Example 3 A commercially available absorbable adhesion prevention barrier, Seprafilm (Kaken Pharmaceutical Co., Ltd., a biodegradable film consisting of sodium hyaluronate:carboxymethylcellulose = 2:1 (mass ratio)) was used.
[0056] The bending resistance, tensile strength, and breaking elongation of the nonwoven fabrics of Example 1 and Comparative Example 1, the tissue substitute artificial fiber fabric of Comparative Example 2, and the Seprafilm of Comparative Example 3 were measured as described above, and the results are shown in Table 1 below.
[0057] [Table 1]
[0058] The nonwoven fabric (adhesion prevention material) of Example 1 is easier to apply to the surface of tissue where adhesion may occur, such as wounds, and has good handleability, compared to Seprafilm of Comparative Example 3. The nonwoven fabric (adhesion prevention material) of Example 1 also has a bending resistance within the range of 20 to 80 mm, and is more excellent in handleability. The nonwoven fabric (adhesion prevention material) of Example 1 has a tensile strength of 10 N or more, and also has good suturing properties after being applied to the surface of tissue where adhesion may occur, such as wounds.
[0059] The nonwoven fabrics of Example 1 and Comparative Example 1, and the oil used in Example 1 were subjected to FTIR analysis as described above, and the results are shown in FIGS. As can be seen from FIGS. 1 to 3, the nonwoven fabric of Example 1 has a wave number of 2860 cm -1 The nonwoven fabric of Comparative Example 1 has a peak at a wavenumber of 2860 cm (surrounded by a dashed line) derived from the oil agent. -1 There is no peak in the vicinity.
[0060] The nonwoven fabrics of Example 1 and Comparative Example 1, the tissue substitute artificial fiber fabric of Comparative Example 2, and Seprafilm of Comparative Example 3 were used as samples to evaluate the adhesion prevention properties of these samples by in vivo testing. The results are shown in Table 3 below.
[0061] In vivo testing After anesthetizing a dog (beagle), the pericardium surrounding the heart was incised, the surface of the heart was scraped with a file-like sponge, a sample was placed on the wounded surface of the heart, and blood was applied to the sample. The pericardium was then sutured and fixed with sutures at several points to prevent the sample from moving. In the case of Reference Example 1, the incision in the pericardium was sutured without placing a sample. After 3 months of implantation or 6 months of implantation, the degree of adhesion between the pericardium and the scraped part of the heart surface was judged by adhesion score to confirm adhesion prevention. In both the 3-month and 6-month implantation periods, the nonwoven fabrics of Example 1 and Comparative Example 1 were used on two dogs, the tissue substitute artificial fiber fabric of Comparative Example 2 and Seprafilm of Comparative Example 3 were used on one dog, and Reference Example 1 was used on two dogs. The criteria for adhesion score are as shown in Table 2 below.
[0062] [Table 2]
[0063] [Table 3]
[0064] The adhesion score after 3 months of implantation in the case of using the nonwoven fabric with the oil solution made of liquid paraffin and polyoxyethylene oleyl ether of Example 1 was 2, and the adhesion score after 3 months of implantation in the case of using the nonwoven fabric from which liquid paraffin and polyoxyethylene oleyl ether of Comparative Example 1 were removed and the tissue substitute artificial fiber fabric of Comparative Example 2 was 3. The nonwoven fabric of Example 1 had high adhesion prevention properties and had adhesion prevention properties equivalent to those of Seprafilm of Comparative Example 3. There is a large difference between the presence or absence of bleeding between adhesion scores 2 and 3, and if bleeding occurs during removal as in adhesion score 3, hemostasis or blood transfusion is required, which takes time for surgery. In addition, although the Seprafilm of Comparative Example 3 had good adhesion prevention properties, it took time to place it on the wounded heart surface during the implantation operation and had poor handleability, whereas the nonwoven fabric of Example 1 was easy to place on the wounded heart surface during the implantation operation and had good handleability. The nonwoven fabric to which the oil agent consisting of liquid paraffin and polyoxyethylene oleyl ether of the embodiment is applied can be suitably used as an adhesion prevention material in surgery for cardiac diseases that require reoperation, such as pediatric cardiac diseases that require surgery every three months.
[0065] The nonwoven fabrics of Example 1 and Comparative Example 1 were used to carry out in vitro tests as described below to confirm their effects on the proliferation of human skin fibroblasts. The results are shown in Table 4 below.
[0066] (In vitro testing) (Test Example 1) A polystyrene plate for tissue culture (TCPS, 24 wells, Corning) was coated with 0.5% PMPC (2-methacryloyloxyethyl phosphorylcholine polymer) and left to dry overnight at room temperature. The nonwoven fabric of Example 1 was placed on the bottom surface of the PMPC-coated TCPS and used as a culture vessel. DMEM (Dulbecco's modified Eagle's medium) / F12 containing 10% FBS (fetal bovine serum) was used as the culture medium. Normal human dermal fibroblast (NHDF) cells (passage number: 5) were seeded at a density of 1.0 × 10 6 cells / well relative to the area of the bottom surface of the culture vessel. 4 cell / cm 2After culturing for 1 hour, 24 hours, 3 days, or 7 days, the cell count was measured using Cell Counting Kit-8.
[0067] (Test Example 2) The number of NHDF cells after culturing for 1 hour, 24 hours, 3 days, or 7 days was measured in the same manner as in Test Example 1, except that the nonwoven fabric of Comparative Example 1 was placed on the bottom surface of the TCPS after PMPC coating and used as a culture vessel.
[0068] (Control Test Example 1) The number of NHDF cells after culturing for 1 hour, 24 hours, 3 days, or 7 days was measured in the same manner as in Test Example 1, except that TCPS was used as the culture vessel.
[0069] [Table 4]
[0070] In Test Example 1, which used the nonwoven fabric to which the oil solution consisting of liquid paraffin and polyoxyethylene oleyl ether of Example 1 was attached, the number of attached cells was reduced in culture for 24 hours or more, particularly in culture for 7 days, as compared with Test Example 1, which used the nonwoven fabric of Comparative Example 1 from which liquid paraffin and polyoxyethylene oleyl ether were removed, and it was confirmed that the nonwoven fabric to which the oil solution consisting of liquid paraffin and polyoxyethylene oleyl ether was attached inhibits the proliferation of NHDF cells. It is presumed that in tissues where adhesions may occur, such as wounds after cardiac surgery, the nonwoven fabric to which the oil solution consisting of liquid paraffin and polyoxyethylene oleyl ether is attached exhibits an adhesion prevention effect by inhibiting the proliferation of fibroblasts, and is excellent in adhesion prevention properties for a long period of time (for example, after the passage of 3 months).
[0071] The nonwoven fabric of Comparative Example 1 and the polyoxyethylene oleyl ether used in Example 1 were analyzed by differential scanning calorimetry as described above, and the results are shown in Fig. 4. In Fig. 4, a is the DSC curve of the nonwoven fabric of Comparative Example 1, b is the DSC curve of polyoxyethylene oleyl ether 1 used in Example 1, and c is the DSC curve of polyoxyethylene oleyl ether 2 used in Example 1. As can be seen from FIG. 4, polyoxyethylene oleyl ether 1 and polyoxyethylene oleyl ether 2 used in Example 1 have intermediate water in which an exothermic peak due to low-temperature crystallization of water is observed at 0°C or less during the temperature rise process in differential scanning calorimetry (DSC) in a wet state. In addition, in the case of the nonwoven fabric of Comparative Example 1, only the endothermic peak of water (contained in the nonwoven fabric) is observed at 0°C. Although this is only speculation, it is speculated that in tissues where adhesion may occur, such as wounds, severe adhesion is suppressed by the synergistic effect of the hydrophobic liquid paraffin attached to the nonwoven fabric of the example and the fibrin deposition inhibitory effect (antithrombotic effect) of the polyoxyethylene oleyl ether having intermediate water when wet, and the adhesion prevention property is improved over a long period of time, for example, after 3 months and / or 6 months.
[0072] The present invention is not particularly limited, but it is desirable to include, for example, the following embodiments. [1] A fiber sheet and an oil agent attached to the fiber sheet, The oil is an adhesion preventing material containing liquid paraffin and a surfactant. [2] The adhesion preventing material according to [1], wherein the oil is attached in an amount of 0.1 to 20% by mass based on the mass of the fiber sheet. [3] The adhesion preventing material according to [1] or [2], wherein the surfactant is a polyoxyethylene alkyl ether. [4] The adhesion preventing material described in [3], wherein the polyoxyethylene alkyl ether includes polyoxyethylene oleyl ether. [5] The adhesion preventing material according to any one of [1] to [4], wherein the surfactant has intermediate water in which, when wet, an exothermic peak due to low-temperature crystallization of water is observed at 0°C or lower during the temperature rise process in differential scanning calorimetry (DSC). [6] The adhesion preventing material according to any one of [1] to [5], wherein the fiber sheet is a nonwoven fabric. [7] The adhesion preventing material described in any of [1] to [6], wherein the fibers constituting the fiber sheet are mainly composed of one or more biocompatible polymers selected from the group consisting of polyglycolic acid, polylactic acid, alginate, cellulose, and carboxymethylcellulose. [8] The adhesion preventing material according to any one of [1] to [7], which has a bending resistance of 20 to 80 mm as measured by a 41.5° cantilever method. [9] Weight is 10 to 200 g / m 2 The adhesion preventing material according to any one of [1] to [8],
[10] The adhesion barrier described in any one of [1] to [9], which has a thickness of 0.1 to 2.0 mm.
[11] Fourier transform ultraviolet spectroscopy-attenuated total reflection measurement at a wave number of 2860 cm -1 The adhesion preventing material according to any one of [1] to
[10] , which has a peak derived from an oil agent in the vicinity of
Claims
1. A fiber sheet and an oil agent attached to the fiber sheet, The oil agent includes liquid paraffin and a surfactant, The surfactant is a polyoxyethylene alkyl ether, The fiber sheet is at least one selected from the group consisting of a woven fabric, a knitted fabric, a nonwoven fabric, and a composite thereof; The fibers constituting the fiber sheet are an adhesion preventing material whose main component is a biocompatible polymer.
2. The adhesion preventing material according to claim 1, wherein the oil is attached in an amount of 0.1 to 20% by mass based on the mass of the fiber sheet.
3. The adhesion preventing material according to claim 1 , wherein the polyoxyethylene alkyl ether comprises polyoxyethylene oleyl ether.
4. The adhesion preventing material according to claim 1, wherein the surfactant has intermediate water in which, when wetted, an exothermic peak due to low-temperature crystallization of water is observed at 0°C or lower during the temperature rise process in differential scanning calorimetry (DSC).
5. The adhesion preventing material according to claim 1 , wherein the fiber sheet is a nonwoven fabric.
6. The adhesion preventing material according to claim 1 , wherein the fibers constituting the fiber sheet are primarily composed of one or more biocompatible polymers selected from the group consisting of polyglycolic acid, polylactic acid, alginate, cellulose, and carboxymethylcellulose.
7. The adhesion preventing material according to claim 1, which has a bending resistance of 20 to 80 mm as measured by a 41.5° cantilever method.
8. Weight per unit area: 10 to 200 g / m 2 The adhesion preventing material according to claim 1 ,
9. The adhesion preventing material according to claim 1, which has a thickness of 0.1 to 2.0 mm.
10. In the analysis by Fourier transform ultraviolet spectroscopy-attenuated total reflection measurement method, the wave number was 2860 cm -1 The adhesion preventing material according to any one of claims 1 to 9, which has a peak derived from an oil agent in the vicinity of
Citation Information
Patent Citations
Medical vaseline ointment gauze and manufacturing method thereof
CN105688252A
Body tissue coalescence preventing film
JP1991000069A
Anti-adhesion material and artificial biological membrane each comprising decellularized tissue
WO2016143746A1
Anti-adhesion composition
WO2019138583A1